How much varietey is in the 'german model' linking establishment employment systems and profiles of innovative capabilities Wie viel heterogenität gibt es im, modell deutschland'? Zur verbindung von betrieblichen beschäftigungssystemen und profilen der innovationsfähigkeit - Kirchner, Stefan; Beyer, Jürgen; Ludwig, Ute (Industrielle Beziehungen - Zeitschrift für Arbeit, Organisation und Management, 2012)
In the past, the German employment system has been considered a precondition for the manufacturing of high-quality products and the typically strong capacity for incremental innovation. This article investigates the relationship between establishment employment systems and innovative capability profiles using data from a representative establishment telephone survey conducted in the fall of 2010 (N = 988). Employing latent class analysis, five different innovative capability profiles are identified. All five profiles show significant association with the included aspects of establishment employment systems. The profiles differ with respect to long-term personnel development as well as decentralized organizational practices. Our results reveal the variety of strategies being pursued within one national institutional framework. In addition, our findings indicate that establishments in the German economic model do not focus exclusively on incremental innovation. Instead we find evidence for complementary combination of radical and incremental innovation activities. © Rainer Hampp Verlag.
CRIS-Team Scopus Importer:2025-04-09
Keywords: Employment systems; Germany; Innovative capabilities; Latent class analysis